2019
DOI: 10.7175/cmi.v12i1.1339
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management and therapy of idiopathic recurrent pericarditis

Abstract: Recurrent pericarditis is defined when pericarditic chest pain reappears after a symptom-free period of at least 4 to 6 weeks and after completion of full-dose anti-inflammatory therapy. Idiopathic pericarditis is the commonest etiology. The diagnosis of idiopathic cases is essentially an exclusion diagnosis, supported by a typical clinical course. The diagnosis is based on the association of typical symptoms and signs: mainly pericarditic chest pain plus pericardial rubs or electrocardiographic alterations or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, CS was not indicated when the CRP level was within normal limits [27]. Assolari et al suggested that CS should be included in case of autoimmune recurrent pericarditis and incomplete response to NSAID and colchicine, but only in combination with these drugs [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, CS was not indicated when the CRP level was within normal limits [27]. Assolari et al suggested that CS should be included in case of autoimmune recurrent pericarditis and incomplete response to NSAID and colchicine, but only in combination with these drugs [31].…”
Section: Discussionmentioning
confidence: 99%
“…While the impact of RP on patients' health-related quality of life (HRQoL) has been reported in the literature [7][8][9][10][11][12] and is thought to be due to the primary symptom of the condition (e.g., chest pain) and the resulting uncertainty and anxiety about new recurrences, impact on HRQoL has not been explicitly evaluated in previous clinical research. In addition, corticosteroids (CS), despite well-known warnings and precautions in patients with cardio-metabolic comorbidities, are widely used to treat RP [13], putting patients at risk for additional adverse events, including recurrence and steroid dependence [14]; comorbidities associated with chronic CS use may also lead to adverse impacts on HRQoL [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of RP on patients' health-related quality of life (HRQoL) has been reported in the literature [1][2][3][4] and is thought to be due to the primary symptom of the condition (e.g., chest pain) and the resulting uncertainty and anxiety of new recurrences, impact to HRQoL has not been explicitly evaluated in previous clinical research. In addition, corticosteroids are widely used to treat RP [5], putting patients at risk for steroid-dependence [6]; comorbidities associated with chronic corticosteroid use may also lead to adverse impacts on HRQoL [7,8].…”
Section: Introductionmentioning
confidence: 99%